Induction of protective cytotoxic T cells with viral proteins. - Bachmann, M; Kündig, T; Freer, G; Li, Y; Kang, C; Bishop, D; Hengartner, H; Zinkernagel, R (1994)
Induction of CD8+, class I-restricted T cells by non-infectious, exogenous antigens has been documented for model protein antigens such as ovalbumin and for major histocompatibility complex restricted short peptides in viral and tumor systems. However, the protective capacity of cytotoxic T cells induced by conventional proteins has not been tested in vivo so far. We, therefore, evaluated the induction of protective cytotoxic T cells against three different full-length recombinant viral proteins derived from a baculovirus expression system, i.e. the glycoprotein and nucleoprotein of lymphocytic choriomeningitis virus (LCMV) and the nucleoprotein of vesicular stomatitis virus (VSV). These viral proteins induced cytotoxic T cells in a T helper cell-independent fashion which lysed infected target cells in vitro and protected mice from viral replication, immunopathological disease and growth of a tumor expressing the same antigen as a tumor antigen. These results are surprising, since it had been shown earlier for completely inactivated nonreplicating viral vaccines and again here for beta-propiolactone-inactivated VSV or UV-light inactivated LCMV that nonreplicating viral vaccines were incapable of inducing protective cytotoxic T cells. Our data show that immunization of mice with as little as 10 micrograms of non-infectious viral proteins triggered long-lasting CD8+ T cell-mediated antiviral immunity. It was found that the protein alone was only weakly able to induce cytotoxic T cells, and that association with cellular debris functioned as an adjuvant. These findings may be relevant for our understanding of the phenomenon of cross-priming and have obvious implications for vaccine strategies.